The ability of Junior High School mathematics teachers writing Higher Order Thinking Skills (HOTS) questions - Hamdi, Syukrul; Kartowagiran, Badrun; Istiyono, Edi; Rahman, Hadi Nur (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2022)
This study is a survey research with a cross sectional survey design, which aims to describe the ability of junior high school mathematics teachers in writing HOTS items. The population of this study was junior high school mathematics teachers in Sleman Regency, while the sample was 21 teachers determined by non-stratified random sampling. The sample teachers came from 11 schools totaling 21 teachers. Each teacher created three HOTS items along with their grids. The question items made by the sample teachers were descriptive questions. The question items that had been prepared were then reviewed by two mathematics teachers from leading junior high schools in Yogyakarta. The next stage after validation is the trial. The number of respondents used was 263 students for testing teacher-made questions, namely 127 students in class VIII and 136 students in class VII. The results showed that the quality of the questions produced by the teacher based on the reliability estimation results obtained an estimate of 0.635 for class VII and 0.416 for class VIII. Likewise, the resulting differentiating power is less than 50% of the questions made by teachers who have differentiating power in the good, good, and very good categories. Factors that cause this include the lack of experience of teachers in writing HOTS questions. This is a special note to familiarize teachers with using HOTS questions in daily tests, UTS, and UAS proportionally so that the experience and ability of teachers to write HOTS questions increases.